CORRELATION BETWEEN PARENTAL INTERACTIONS WITH ONLINE GAME ADDICTED ADOLESCENTS - DHIA DIANA FITRIANI; FRIDA KASUMAWATI; R TRI RAHAYUNING LESTARI; AYU HERAWANTI (NURSING ANALYSIS: Journal of Nursing Research, 2022)
ABSTRACT WHO defines online game addiction as a mental disorder that is included in (ICD-11). Smartphone users in Indonesia reach approximately 82 million and more than 52 million are online game players. This puts Indonesia in the 17th position in the world as the most online game players. Online game addiction can have physical and mental impacts. The purpose of this study was identified the correlation between parental interactions with online game addicted adolescents. This research method was cross sectional design, non-probability sampling technique, total sampling, 55 respondents. The results of this study indicated that there was a correlation between the parental interaction with online game addicted adolescents (p=0.000). Lack of parental interaction with adolescents can lead to adolescents behaviour changes like online games addiction. Parents as the closest environment to adolescents must be able to know how to communicate and interact according to the stage of adolescent development. The implications of the results of this study were expected to increase the role of nurses, especially in the field of mental and community nursing practice in providing health education regarding the role of parents in adolescent behaviour, growth, and development. Keywords: Addiction, Adolescent, Interaction, Online Game, Parents KORELASI INTERAKSI ORANG TUA DENGAN REMAJA KECANDUAN ONLINE GAME ABSTRAKWHO mendefinisikan kecanduan online game sebagai gangguan mental yang dimasukkan ke dalam (ICD-11). Berdasarkan laporan We Are Social per Januari 2022, Indonesia menjadi negara dengan jumlah pemain game terbanyak ketiga di dunia. Kecanduan online game dapat menimbulkan dampak fisik dan mental. Tujuan penelitian ini untuk mengidentifikasi korelasi interaksi orang tua dengan remaja kecanduan online game. Metode penelitian ini dengan desain cross sectional, teknik non-probabilitiy sampling, total sampling sejumlah 55 responden. Hasil penelitian ini menunjukkan bahwa ada hubungan antara interaksi orang tua dengan remaja online game (p=0,000). Kurangnya interaksi orang tua dengan remaja dapat menyebabkan perubahan perilaku pada remaja seperti kecanduan online game. Orang tua sebagai lingkungan terdekat dengan remaja harus dapat mengetahui cara berkomunikasi dan berinteraksi sesuai dengan tahap perkembangan remaja. Implikasi hasil penelitian ini diharapkan dapat meningkatkan peran perawat terutama bidang praktik keperawatan jiwa dan komunitas dalam memberikan pendidikan kesehatan mengenai peran orang tua terhadap tumbuh kembang dan perilaku remaja. Kata Kunci: Interaksi, Kecanduan, Online Game, Orang Tua, Remaja